Comparison of characteristics between neuropathic pain and non-neuropathic pain in patients with diabetic carpal tunnel syndrome: A cross-sectional study - Liu, Yingnan; Zhuang, Yongqing; Wei, Ruihong; Tan, Zhouyong; Chen, Chao; Yang, Dazhi (Frontiers in Surgery, 2022)
Background: The aim of the study was to compare the clinical characteristics of diabetic carpal tunnel syndrome between patients with neuropathic pain (NeuP) and non-NeuP. Methods: We enrolled 276 patients with diabetic carpal tunnel syndrome. Pain symptoms were evaluated using a visual analog scale. Douleur Neuropathique 4, the Neuropathic Pain Symptoms Inventory questionnaire, and the body map were used to assess neuropathic symptoms. Baseline information, clinical manifestations, electrophysiological test results, and psychological status were compared between the neuropathic pain (NeuP) and non-NeuP to identify the risk factor for NeuP occurrence. Results: Results showed that the degree of pain was more severe in NeuP patients than in nociceptive pain patients (p = 0.025). The frequencies of light touch and pinprick were more pronounced in the NeuP group than in the non-NeuP group (light touch: p = 0.001; pinprick: p = 0.004). There were 48 and 27 NeuP patients with extramedian and proximal spread, respectively, whereas in the non-NeuP group, there were 11 and 9 patients, respectively (p = 0.03). Electrophysiological results showed that patients in the NeuP group exhibited greater sensory nerve conduction velocity impairment compared with the non-NeuP group (p = 0.033). Pain Catastrophizing Scale total scores of the NeuP group were significantly higher than those of the non-NeuP group (p = 0.006). Conclusion: Of the 276 diabetic carpal tunnel syndrome patients studied, the majority had NeuP. Furthermore, light touch, electrophysiological test results, and psychological factors were found to be related to NeuP occurrence in patients with diabetic carpal tunnel syndrome.